2005
DOI: 10.1080/00288330.2005.9517314
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of the southern rock lobster,Jasus edwardsii,off South Australia

Abstract: Movement patterns of the southern rock lobster Jasus edwardsii were determined from 14 280 tag-recapture events across South Australia between 1993 and 2003. In total, 68% of lobsters were recaptured within 1 km of their release site and 85% within 5 km. The proportion of lobsters moving >1 km in marine fishing areas (MFAs) ranged from 13% to 51%. Movement rates were noticeably high in the south-east and at Gleesons Landing lobster sanctuary off the Yorke Peninsula but patterns of movement differed spatially. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The available data for several decapod species indicate that there is a relatively poor correlation between locomotor activity, home range size, and animal size. Some studies found no relationship (Watson et al 1999;Gherardi et al 2000;Comeau and Savoie 2001;Stone and O'Clair 2002;Cooke 2004;Golet et al 2006), while others found smaller animals moved farther (Kelly and MacDiarmid 2003;Linnane et al 2005). In this study, due to the size of the transmitter, the smallest lobster we could track was 62 mm CL, and due to availability in our study area, the largest was 93 mm CL.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The available data for several decapod species indicate that there is a relatively poor correlation between locomotor activity, home range size, and animal size. Some studies found no relationship (Watson et al 1999;Gherardi et al 2000;Comeau and Savoie 2001;Stone and O'Clair 2002;Cooke 2004;Golet et al 2006), while others found smaller animals moved farther (Kelly and MacDiarmid 2003;Linnane et al 2005). In this study, due to the size of the transmitter, the smallest lobster we could track was 62 mm CL, and due to availability in our study area, the largest was 93 mm CL.…”
Section: Discussionmentioning
confidence: 80%
“…These studies have consistently shown that: (1) most lobsters, within the time frame that they were tracked, remained in the vicinity of the area where they were initially tagged, or traveled 55 km; and (2) in any given habitat or area there appear to be lobsters that are either residents or transients (spiny lobsters: Panulirus argus [Herrnkind and McLean 1971;Herrnking 1980]; Jasus edwardsii [Kelly 2001;Kelly and MacDiarmid 2003;Linnane et al 2005]; Panulirus cygnus [MacArthur et al 2008]; clawed lobsters: Homarus gammarus [Smith et al 1998]; Homarus americanus [Dow 1974;Watson et al 1999;Bowlby et al 2007]; reviewed by Cooper and Uzmann 1980, Krouse 1980, Haakonsen and Anoruo 1994, Lawton and Lavalli 1995, Childress and Jury 2006. Additional studies have used the distance a displaced lobster will travel to reach its shelter or a baited trap as a technique for estimating a lobster's home range.…”
Section: Introductionmentioning
confidence: 99%
“…In LenMod, growth is estimated using a lengthtransition matrix and is defined as the proportion of lobsters in each length category that grow into larger length classes during each seasonal moulting period (Hobday & Punt 2001). The length-transition matrix has been created using the extensive tagrecovery data set for the SZ (Linnane et al 2005) and incorporates known information on sex ratios as well as annual within-season moulting periods. A key feature of LenMod is the ability to account for slower growth rates of females that have reached sexual maturity (McGarvey & Feenstra 2001) thus allowing a more accurate overall estimation of growth than previously assumed using a traditional von Bertalanffy mean growth curve.…”
Section: Model Estimatesmentioning
confidence: 99%
“…Large males also showed greater site association than small males, however, the increase was more of a step function occurring at 130 mm CL (Kelly & MacDiarmid 2003). Linnane et al (2005) found that immature J. edwardsii females exhibited the greatest movement rates in South Australia. Heupel et al (2006) reviewed different strategies of deployment of acoustic receivers with cost and benefit analysis of these deployment designs.…”
Section: Nomadism and Emigrationmentioning
confidence: 99%
“…Studies designed directly to determine movement patterns of adult lobsters have used techniques such as tag-recapture (e.g., Gardner et al 2002;Kelly & MacDiarmid 2003;Linnane et al 2005), visual tracking, acoustic telemetry (e.g., Kelly 2001;Hovel & Lowe 2007), or a combination of all these techniques . Although each technique has strengths and weaknesses (see Herrnkind 1980), both reviews (Herrnkind 1980;Childress & Jury 2006) noted the potential of acoustic telemetry.…”
Section: Introductionmentioning
confidence: 99%